Educational Justice and Disability: The Limits of Integration - Evans, Brigid (Philosophical Inquiry in Education, 2021)
Integration as a requirement of social justice is generating much enthusiasm in political philosophy. In The Imperative of Integration (2010), Elizabeth Anderson defines integration as involving and furthering “the free interaction of citizens from all walks of life in terms of equality and mutual regard”(Anderson, 2010, p. 95). However, this idea of integration as a moral imperative is yet to be tested in the case of students with an intellectual or behavioural disability (I/BD), a small group with complex and diverse educational needs. While “inclusive” schools may be increasingly the norm in Western education systems, it is not self-evident that the imperative of integration ought to carry over into special education. ⁠Focusing on the unique concerns for integrating students with an I/BD into generalist classrooms, I aim to describe the moral constraints that ought to be imposed on the process of integration.The concerns for integrating students with an I/BD will be framed as a question of the just distribution of costs associated with bringing about integration. It will be argued that, within the context of education, the imperative of integration is unjust if it unduly burdens students with an I/BD, perpetuates the harms it proposes to resolve, or results in a failure to provide the educational goods owed to students. As schools are specially tasked with the provision of educational goods in society, educational costs are more ethically significant in the given context than the costs of not integrating. Educational institutions should still play a role in achieving an integrated society through just means. This must be done by shifting the burdens of integration off students with an I/BD and onto the education system.